Proses Politik dan Administrasi dalam Implementasi Kebijakan Penyelenggaraan Pembauran Kebangsaan di Daerah: Studi BAKESBANGPOL Prov. KEPRI - Yanuard, Yunus; Samin, Rumzi; Kurnianingsih, Fitri (Jayapangus Press, 2024)
The implementation of national integration policies in a region related to nation-building and politics is a complex and relevant issue that requires an effective and efficient political and administrative process. This study aims to analyze the Grindle theory on the case study of the guidelines for implementing national renewal in the province of KEPRI. The research method used is a descriptive-qualitative approach to study the political and administrative process by collecting and analyzing relevant data according to the phenomenon. The results and discussion show that the process of politics and administration based on the Grindle theory includes implementing policies divided into two aspects, namely the content of policy and the context of implementation, each having a role for actors. The findings of the Forum for National Awakening (FPK) in KEPRI play a crucial role in promoting national unity and cohesion among various ethnic groups, tribes, and communities. In the implementation of policies and administration, FPK has shown its commitment to maintaining national unity and increasing public awareness and harmony. The forum also plays a role as a mediator in resolving conflicts that arise and helps the provincial government to maintain national unity. However, there are several challenges and obstacles that will be faced in the implementation of this policy in the future. One of the challenges is the difference in opinions and visions among stakeholders involved in national integration activities. Another challenge is how to increase public awareness and harmony regarding national values. Therefore, the implementation of National Integration Policy in KEPRI still requires special attention and commitment from all relevant parties.